CHIEFTAINCY SUCCESSION CONFLICTS IN THE BUNKPURUGU TRADITIONAL AREA, NORTH EAST, GHANA - Yaro, S. D.; Ngmenkpieo, F. (UDS International Journal of Development, 2020)
The once cohesive family of Louk has now become a host to many chieftaincy successions dispute. This situation has pushed the researchers to investigate the sources of the chieftaincy succession disputes in Bunkpurugu and their manifestations in Bunkpurugu Traditional Area. To arrive at this, a pragmatic research philosophy was adopted and a deductive and inductive theory development approach was deemed fit for the study. The design employed were both qualitative and quantitative and the data was collected using questionnaires, interview guides, and focused group discussions. The primary data gathered were complemented by extensive literature review on chieftaincy succession disputes in Ghana and Africa as a whole. The analysis of the data was done using content analysis and the Statistical Package for Social Sciences (SPSS) revealed that the main sources of the dispute were the commodification of thrones, desire to control resources and political influence. It also revealed that the manifestation of the conflict in Bunkpurugu Traditional Area was a stern power struggle between the Jafouk family and the Jamong family. Effects of the dispute include division among the people, avoidance of social functions like funerals and naming ceremonies and disloyalty to the Jafouk Leader (Bunkpurugu chief). Keywords: North East Region, Bunkpurugu, Chieftaincy, Bimobas, Dispute